Biocompatibility assay of cellular behavior inside a leaf-inspired biomimetic microdevice at the single-cell level. Issue 52 (27th June 2017) - Wu, Wenming; Manz, Andreas
Abstract : Inspired by recent studies, we created a biomimetic method to replicate the veinal microvasculature from a natural leaf into a lab-on-a-chip system, which could be further utilized as a biomimetic animal vessel as well as in vessel-derived downstream applications. Abstract : Herein, we introduce a practical and effective manufacturing methodology for a biomimetic microdevice replicated from the Tilia platyphyllos leaf. With this method, artificial microchambers (of controllable dimension and depth) can be easily integrated into leaf-inspired whole-ordered venation patterns. To display the biocompatibility of this microdevice, we applied it to a long-term (seven days) cell culture and monitored the results. Based on a comprehensive biophysical analysis, including covering cellular deformation, cell migration, cytomembrane tension, extracellular communication, protonema formation, microvilli, and the tethers' dynamic of human melanoma cells inside the device at a single-cell resolution, we were able to verify for the first time a leaf-inspired PDMS microdevice as a biocompatible platform for mammal cell culture, showing promise that such a biomimetic device could be further applied for organ-on-a-chip studies and other biomedical research.